2019
DOI: 10.3390/ijerph17010084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use Conversion on Surface Soil Heavy Metal Contamination in a Typical Karst Plateau Lakeshore Wetland of Southwest China

Abstract: Land use conversion could directly or indirectly influence heavy metal geochemistry by changing soil properties. The aim of this study was to explore the effect of land use conversion on surface soil heavy metal contamination in the karst plateau lakeshore wetlands of Southwest China. Based on this, a total of 120 soil samples were collected from 30 sites from different types of land uses (farmlands, grasslands and woodlands) around a lake in Suohuangcang National Wetland Park in August 2017. Contents of As, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A comparison with the metal concentrations reported in the soil of several locations in India and the world (Amouei et al., 2018; Benjamin et al. 2021; Khan & Kathi, 2014; Kim et al., 2020; Kladsomboon et al., 2020; Quan et al., 2015; Rao et al., 2014; Sakram et al., 2015; Sun et al., 2019; Yaylalı‐Abanuz, 2011) is summarized in Exhibit 8. It may be readily observed that the concentrations of Ba, Fe, Mn, and Pb found in the soil of the Raipur region are particularly high, calling for urgent action to control industrial effluents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison with the metal concentrations reported in the soil of several locations in India and the world (Amouei et al., 2018; Benjamin et al. 2021; Khan & Kathi, 2014; Kim et al., 2020; Kladsomboon et al., 2020; Quan et al., 2015; Rao et al., 2014; Sakram et al., 2015; Sun et al., 2019; Yaylalı‐Abanuz, 2011) is summarized in Exhibit 8. It may be readily observed that the concentrations of Ba, Fe, Mn, and Pb found in the soil of the Raipur region are particularly high, calling for urgent action to control industrial effluents.…”
Section: Resultsmentioning
confidence: 99%
“…parable concentrations of these elements in the soils at various locations of India and other countries have been reported (Amouei et al, 2018;Benjamin et al, 2021;Khan & Kathi, 2014;Kim et al, 2020;Kladsomboon et al, 2020;Quan et al, 2015;Rao et al, 2014;Sakram et al, 2015;Sun et al, 2019;Yaylalı-Abanuz, 2011).…”
Section: Metal Concentrationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because soils are a major sink for heavy metals, the sediment contains a record of pollution in the area. Moreover, when environmental conditions (e.g., temperature, pH, and organic matter content) change, heavy metals may be redistributed in the sediment, causing secondary contamination [15,16]. Thus, establishing the sequence of sedimentary ages can reveal the historical inputs and associated trends in heavy metal pollution.…”
Section: Introductionmentioning
confidence: 99%
“…With industrial development, environmental heavy metal contamination is becoming a serious problem and requires urgent remediation [ 1 ]. For example, heavy metals were detected in the soil of woodlands, grasslands, and farmlands in Suohuangcang National Wetland Park [ 2 ]. This kind of contamination can affect food, like fish, crops, and water.…”
Section: Introductionmentioning
confidence: 99%